React and React Native. - Mikhail Sakhniuk; Adam Boduch; PACKT (GB: Packt, 2024)
Get a big-picture view of modern React and React Native and see how they go hand-in-hand - covering TypeScript development, Vite, state management strategies, unit testing with Jest, and more. Purchase of the print or Kindle book includes a free PDF eBook. Key Features New content on TypeScript, React frameworks, state management strategies, and unit testing Get to grips with React fundamentals and modern React techniques and architecture Broaden your React expertise through mobile development with React Native Book Description Welcome to your big-picture guide to the React ecosystem. If you're new to React and looking to become a professional React developer, this book is for you. This updated fifth edition reflects the current state of React, including React framework coverage as well as TypeScript. Part 1 introduces you to React. You'll discover JSX syntax, hooks, functional components, and event handling, learn techniques to fetch data from a server, and tackle the tricky problem of state management. Once you're comfortable with writing React in JavaScript, you'll pick up TypeScript development in later chapters. Part 2 transitions you into React Native for mobile development. React Native goes hand-in-hand with React. With your React knowledge behind you, you'll appreciate where and how React Native differs as you write shared components for Android and iOS apps. You'll learn how to build responsive layouts, use animations, and implement geolocation. By the end of this book, you'll have a big-picture view of React and React Native and be able to build applications with both. What you will learn Explore React architecture, component properties, state, and context Work with React Hooks for handling functions and components Fetch data from a server using the Fetch API, GraphQL, and WebSockets Dive into internal and external state management strategies Build robust user interfaces (UIs) for mobile and desktop apps using Material-UI Perform unit testing for your components with Vitest and mocking Manage app performance with server-side rendering, lazy components, and Suspense Who this book is for This book is for any JavaScript or TypeScript developer who wants to start learning how to use React and React Native for web and mobile app development. No prior knowledge of React or React Native is required. However, a working knowledge of JavaScript is necessary to be able to follow along the content covered.
Data in extended ASCII character set.
Mode of access: Internet.